The Administration of the Bankruptcy Estate according to the Bavarian Code of Civil Procedure of 1869 with a View to the Prussian Bankruptcy Code of 1855 and the Reich Bankruptcy Code of 1877 - Martin Löhnig (Journal on European History of Law)
The bankruptcy proceedings codified in the Bavarian Code of Civil Procedure immediately before the founding of the German Empire after long scientific and political discussion (Gant) competed as the most up-to-date regulation of the bankruptcy proceedings in a German individual state with the regulatory concepts of the Prussian Bankruptcy Code of 1855, which was significantly influenced by French law, for influence on the Reich Bankruptcy Code of 1877. It is therefore necessary to examine what impetus the Bavarian law was able to provide, which will be done using the example of the problem of selecting the bankruptcy trustee which is a crucial question in bankruptcy proceedings.